Oxyhydroxide Nanosheets with Highly Efficient Electron–Hole Pair Separation for Hydrogen Evolution. Issue 6 (6th January 2016) - Huang, Junheng; Shang, Qichao; Huang, Yuanyuan; Tang, Fumin; Zhang, Qun; Liu, Qinghua; Jiang, Shan; Hu, Fengchun; Liu, Wei; Luo, Yi; Yao, Tao; Jiang, Yong; et al.
Abstract: The facile electron–hole pair recombination in earth‐abundant transition‐metal oxides is a major limitation for the development of highly efficient hydrogen evolution photocatalysts. In this work, the thickness of a layered β‐CoOOH semiconductor that contains metal/hydroxy groups was reduced to obtain an atomically thin, two‐dimensional nanostructure. Analysis by ultrafast transient absorption spectroscopy revealed that electron–hole recombination is almost suppressed in the as‐prepared 1.3 nm thick β‐CoOOH nanosheet, which leads to prominent electron–hole separation efficiencies of 60–90 % upon irradiation at 350–450 nm, which are ten times higher than those of the bulk counterpart. X‐ray absorption spectroscopy and first‐principles calculations demonstrate that [HO−CoO6− x ] species on the nanosheet surface promote H + adsorption and H2 desorption. An aqueous suspension of the β‐CoOOH nanosheets exhibited a high hydrogen production rate of 160 μmol g −1 h −1 even when the system was operated for hundreds of hours. Abstract : The thickness of a layered β‐CoOOH semiconductor was reduced to obtain an atomically thin two‐dimensional nanostructure. Electron–hole recombination is almost suppressed in the 1.3 nm thick β‐CoOOH nanosheet, which leads to excellent electron–hole separation efficiencies and superior hydrogen production rates ( L D⊥ : carrier diffusion length along the c axis).